Study guides

Q: What is the answer to 5p plus 14 equals 4p-1?

Write your answer...

Submit

Related questions

5p-14 = 8p +4 take the 14 to the other side and the 8p to the other side so 5p-8p = 4 +14 -3p = 18 p = -18/3

5p + 4y

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

42p-1 = 5p+4 42p = 5p+5 37p = 5 p = 5/37 p = 0.135135...

5P + 111 + 136 + 20 = 4c + 4 5P + 267 = 4c + 4 -4 -4 5P + 263 = 4c You cannot cimplify it anymore, unless by 'c' you meant 'P'. 5P + 263 = 4P -5P -5P 263(-1) = -P(-1) -263 = P

p=10/3 or 3.33333333333333333333333333333333333333333333333333333333333333333333333333333

p=1

5p-1=2p-20 3p=21 p=7

20 = 4p + 5 +p 20 = 5p + 5 5p = 20 - 5 = 15 5p = 15 p = 15/5 = 3

==>-3p+7=5-8p+6 ==>5p+7=11 ==>5p=4 ==>p=4/5

3p + 4p +10 = 5p + 2 Subtracting 5p from both sides: 3p + 4p - 5p + 10 = 5p + 2 - 5p ie 2p + 10 = 2 Subtract 10 from both sides: 2p + 10 - 10 = 2 - 10 ie 2p = -8 Divide both sides by 2: p = -4

5p-15 = 15-5p 5p+5p = 15+15 10p = 30 p = 3

5p+18 = 8p Subtract 5p from both sides: 18 = 3p Divide both sides by 3: 6 = p or as p = 6

3p + 18 = 5p + 4Subtract 4 from both sides3p + 14 = 5pSubtract 3p from both sides14 = 2pDivide both sides by 27 = pNote : For presentation purposes the unknown or variable is normally put as the subject of the equation. The answer is then presented as p = 7.

15 = 5 +( 9p - 4p) 15 = 5 + 5p 15 - 5= 5 -5 +5p 10 = 5p there for p = 10/5 = 2

8 + 5p + 7q + 9 + 3p Reordering: 8 + 9 + 5p + 3p + 7q Combine like terms: 17 + 8p + 7q

2p2-5p+2 = 0 (2p-1)(p-2) = 0 p = 1/2 and p = 2

(p + 12)(p - 7) p = 7, -12

-35

10p + 5p - p = 15p - p = 14p

That completely depends on the value of 'p'. Every different value of 'p' gives a different answer.

The equation 45p take away 6p equals too 5p plus 4. This is taught in math.

(5p - 2)(p - 4)

2x+a=p 2x=p-a x=.5p-.5a

well as if i know it might be 5p